AIEgen‐Based Lifetime‐Probes for Precise Furin Quantification and Identification of Cell Subtypes. Issue 45 (23rd September 2021) - Jia, Hui; Ding, Defang; Hu, Jingjing; Dai, Jun; Yang, Juliang; Li, Guogang; Lou, Xiaoding; Xia, Fan
Abstract: Biochemical sensing probes based on aggregation‐induced‐emission luminogens (AIEgens) are widely used in biological imaging and therapy, chemical sensing, and material sciences. However, it is still a great challenge to quantify the targets through fluorescence intensity of AIEgen probes due to their undesirable aggregations. Here, a PyTPA‐ZGO probe with three lifetime signals for precise quantification of furin is constructed: the lifetime signal 1 and signal 2 comes from AIEgen PyTPA‐P (τPn ) and inorganic nanoparticles Zn2 GeO4 :Mn 2+ ‐NH2 (τZn ), respectively, while the lifetime signal 3 is marked as the composite dual‐lifetime signal (CDLSn, C D L S n = τ Z n τ P n ). In contrast, the fluorescence intensity signal of PyTPA‐P shows defectively quantitative performance. Furthermore, it is found that the CDLSn exhibits higher significant differences than the two other lifetime signals (τPn and τZn ) thanks to its wide range between the maximum and minimum signal values and small standard deviation. Therefore, CDLSn is further used to accurately identify cell subtypes based on the specific concentration of furin in each subtype. The lifetime criterion can realize precise quantification, and it should be a promising direction of AIEgen‐based quantitative analysis in the future. Abstract : An aggregation‐induced‐emission luminogen (AIEgen)‐based PyTPA‐ZGO probe with three lifetime signals is proposed for precise furin quantification, including signal 1 of AIEgen (τP n ), signal 2 of inorganic nanoparticles (τZ n ), and signal 3 as the composite dual‐lifetime signal (CDLS n ). Furthermore, CDLS n exhibits higher accuracy than τP n and τZ n in identifying cell subtypes based on the specific furin concentration in each subtype.